Air Pollution Exposure Induces Vascular Injury and Hampers Endothelial Repair by Altering Progenitor and Stem Cells Functionality - Costa, Alice; Pasquinelli, Gianandrea (Frontiers in Cell and Developmental Biology, 2022)
Graphical Abstract